PENGARUH PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH DI BANK MANDIRI TASPEN KOTA SUNGAI PENUH - Iin Syofia Yandra (Jurnal Ekonomi Sakti, 2022)
Abstract This study aims to determine whether service and product quality affect the satisfaction at Bank Mandiri Taspen Sungai Penuh both simultaneously and partially and how much influence. The type of research used is field research with the quantitative approach. The selection of samples using purposive sampling technique so that the number of samples is 30 customers. Hypothesis testing in this study carried out by multiple linear regression. The results of the study using the F test indicate that service and product quality simultaneously have a significant effect on the satisfaction with a significant value of 0,000 < α (0.05). Based on the t test or partial effect, service have a significant effect on satisfaction with a significant value of 0,001 < α (0.05) and product quality have a significant effect on satisfaction with a significant value of 0.000> α (0.05).